Stress analysis on truck chassis - Mohd Husaini, Abd Wahab (2009)
Truck chassis forms the structural backbone of a commercial vehicle. The main function of the truck chassis is to support the components and load that mounted on it. The chassis is experienced a stress whether when it is moving or in a static condition. This paper presents an analysis of the static stress that acting on the upper surface of the truck chassis. These projects study the distributions of the stress that acting on the chassis. Critical parts that will lead to failure are also observed. The method used in this numerical analysis is finite element analysis (FEA). Finite element analysis helps in accelerating design and development process by minimizing number of physical tests, thereby reducing the cost and time for analysis. The commercial finite element package Algor was used for this simulation. 3-D model of the truck chassis was draw by using SolidWorks before analyzed into the simulation software. Numerical results showed that critical part was at the mounting bracket of the tire and also at the front part of the chassis. Some modifications are also suggested to reduce the stress and to improve the strength of the truck chassis.